Some aspects of hemodynamic disorders in patients with severe withdrawal syndrome - A. I. Gozhenko; V. A. Petrov (Journal of Education, Health and Sport, 2017)
Arterial hypertension - the most common cardiovascular syndrome in many countries of the world. Up to 40-50% of the adult population of economically developed countries has an arterial pressure in excess of 140/90 mm Hg. Art. The author discusses the results of research conducted in 2010 -2012 inthe department of resuscitation and intensive care of theChernivtsiRegionalPsychiatric Hospital. 40 patients were examined: Group 1 - 20 patients diagnosed with withdrawal due to delirium alcohol. The results indicate significant hemodynamic disturbances in patients with withdrawal due to the use of delirium alcohol and patients with threatened delirium during hospitalization.